A production method of tin-lead-zinc bronze rod

By introducing a refiner and improving the crystallizer structure in the production of tin and lead zinc bronze rods, the segregation problem of tin and lead is solved, and the strength and surface quality of the material are improved.

CN116536536BActive Publication Date: 2025-03-28JINTIAN COPPER GROUP CORP NINGBO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310375524.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-11
Publication Date
2025-03-28
Estimated Expiration
2043-04-11

AI Technical Summary

Technical Problem

There are problems of reverse segregation of tin and gravity segregation of lead in the production of existing tin-lead-zinc-bronze rods, resulting in reduced material strength, easy cracking, and rough processing surface.

Method used

A flux diffusion tool is used to introduce a refining agent composed of nitride, carbide and oxide into the alloy melt, so as to achieve grain refinement through nucleation, reduce the degree of segregation, and enhance the cooling strength by improving the crystallizer structure.

Benefits of technology

It effectively reduces the segregation degree of tin and lead, improves the strength and surface quality of the material, reduces the surface roughness, and improves machining performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116536536B_ABST
    Figure CN116536536B_ABST
Patent Text Reader

Abstract

The present invention provides a production method of tin-lead-zinc bronze rods, comprising the following steps: S1, adding copper raw materials into a medium frequency melting furnace for melting; S2, after the copper raw materials are melted, adding slag cleaning agent, refining agent and refiner into the medium frequency melting furnace by using a flux diffusion tool; S3, sampling and testing the components from the medium frequency melting furnace, and diluting or compensating according to the components; S4, transferring the molten copper to a holding furnace and then casting by a horizontal continuous casting method to obtain tin-lead-zinc bronze rods. The present invention introduces a grain refiner into the melt by a flux diffusion tool, so that the refiner is evenly distributed in the melt, and relies on the nucleation effect of the refiner to achieve grain refinement and obtain a fine-grained structure, thereby evenly distributing tin and lead, reducing the degree of segregation, and reducing the chain-like low-melting-point substances on the grain boundaries, and solving the dendrite problem, thereby improving the strength of the material and reducing the surface roughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallurgy, and in particular to a production method of tin-lead-zinc bronze rods. Background Art

[0002] Tin-lead-zinc bronze is a high-performance copper alloy material with good wear resistance, friction reduction, corrosion resistance, easy cutting and welding. It is widely used in bearings, bushings, piston rings, valve components, sealing rings, auto parts and gears. Copper is the main component of tin-lead-zinc bronze. Adding tin and zinc can improve the strength of the bronze alloy, making it have high load-bearing capacity and the ability to withstand impact. Adding lead can reduce the friction coefficient of the bronze alloy and improve wear resistance and cutting properties.

[0003] In the prior art, tin-lead-zinc bronze bars are generally produced by continuous casting, and the specific steps are as follows: smelting → continuous casting → peeling → sizing → packaging, among which smelting and continuous casting are the key steps. The tin-lead-zinc bronze currently produced has the problems of reverse segregation of tin and gravity segregation of lead, which will seriously affect the performance of the alloy, resulting in reduced material strength, easy cracking, rough surface of the processed parts, roughness of more than 2.5μm, and easy surface peeling. Summary of the invention

[0004] The technical problem to be solved by the present invention is how to reduce the segregation degree of tin-lead-zinc bronze rods, thereby improving the performance of the material and improving the surface quality.

[0005] In order to solve the above technical problems, the present invention provides a method for producing a zinc bronze rod, comprising the following steps:

[0006] S1. Add copper raw materials into a medium frequency melting furnace for melting;

[0007] S2. After the copper raw material is melted, a slag cleaning agent, a refining agent and a refiner are added into a medium frequency melting furnace by a flux diffusion tool, wherein the refiner is composed of nitride, carbide and oxide, wherein the nitride is titanium nitride and / or aluminum nitride, the carbide is tungsten carbide and / or vanadium carbide, and the oxide is α-Al2O3;

[0008] S3. Take samples from the medium frequency melting furnace for testing, dilute or compensate according to the composition, selectively add copper, tin ingots, lead ingots, and zinc ingots, and control the alloy to contain the following mass percentages: 4.0-6.0% Sn, 0.01-0.05% P, <0.3% Fe, 4.5-6.0% Zn, 4.0-5.7% Pb, <1.5% Ni, <0.1% unavoidable impurities, and the balance is Cu;

[0009] S4. After transferring the molten copper to a holding furnace, horizontal continuous casting is used for drawing to obtain tin-lead-zinc bronze bars.

[0010] Since the smelting temperature of tin-lead-zinc bronze is high, and the temperature range of its crystallizer is relatively large, and there are many impurities, the fluidity of the material is poor, resulting in serious segregation and coarse dendrites, which is not conducive to obtaining bronze materials with uniform composition and smooth processing. The present invention introduces a grain refiner into the alloy melt through a flux diffusion tool, so that the refiner is evenly distributed in the melt, and relies on the nucleation effect of the refiner to achieve grain refinement and obtain a fine-grained structure, thereby making tin and lead evenly distributed, reducing the degree of segregation, and reducing the chain-like low-melting-point substances on the grain boundary, and solving the dendrite problem, thereby improving the strength of the material and reducing the surface roughness.

[0011] In a preferred or optional embodiment, in the refiner, the mass fraction of the nitride is 20-35%, the mass fraction of the carbide is 20-35%, and the mass fraction of the oxide is 35-50%. The refiner used in the present invention is composed of specific nitrides, carbides and oxides, has ultra-high temperature stability, can form heterogeneous nuclei at melting temperatures, and is conducive to grain refinement.

[0012] In a preferred or optional embodiment, in step S2, the amount of the refiner is 0.1-0.8% of the mass of the melt. When the amount of the refiner is within the specified range, the material has the best structural uniformity. If the amount is too small, there will still be dendrite problems. If the amount is too large, it is not conducive to uniform distribution of components.

[0013] In a preferred or optional embodiment, the flux diffusion tooling includes a mixing chamber and a diffusion tube, the mixing chamber is connected to the diffusion tube through a powder delivery tube, the diffusion tube is provided with a plurality of injection holes along the length direction, the mixing chamber is provided with a feed port at the top, an air inlet at the side, and an air blow port at the bottom, the mixing chamber is provided with an air flotation mesh plate, the air flotation mesh plate is provided with a plurality of injection holes, and the air inlet and the air blow port are connected to a nitrogen pipe. A special flux diffusion tooling is used to blow the refiner into the melt, and the powder is blown out from the diffusion tube to achieve uniform distribution in the melt, solving the problem that the traditional stirring method cannot make the flux dispersed evenly.

[0014] In a preferred or optional embodiment, in step S4, the crystallizer used for horizontal continuous casting includes a primary cooling tool, a secondary cooling tool and a water outlet jacket connected in sequence, the casting holes of the primary cooling tool and the secondary cooling tool are connected, the primary cooling tool includes a first outer shell, a first inner sleeve and a first sleeve arranged in sequence from the outside to the inside, a separator ring is provided between the first outer shell and the first inner sleeve, the separator ring divides the space between the first outer shell and the first inner sleeve into a first water inlet chamber and a first water outlet chamber, the first water inlet chamber is connected to at least one first water inlet pipe, and the first water outlet chamber is connected to at least A first water outlet pipe is connected to the first inner sleeve, the space between the first inner sleeve and the first sleeve constitutes a cooling chamber, the secondary cooling fixture includes a second outer shell and a second sleeve arranged from outside to inside, the space between the second outer shell and the second sleeve constitutes a second water inlet chamber, the second water inlet chamber is connected to at least one second water inlet pipe, a second water inlet channel is formed between the second sleeve and the primary cooling fixture, a second water outlet channel is formed between the second sleeve and the water outlet sleeve, the second water inlet channel and the second water outlet channel are connected to the second water inlet chamber, and the water outlet sleeve is connected to at least one second water outlet pipe. Improving the structure of the crystallizer can improve the cooling intensity, and designing the secondary cooling fixture to improve the axial temperature gradient, thereby reducing the existence of segregation and improving material properties.

[0015] In a preferred or optional embodiment, a nitrogen port is provided at the connection portion between the primary cooling fixture and the secondary cooling fixture, and a nitrogen channel connected to the nitrogen port is provided on the crystallizer. Gas protection can be formed by filling with nitrogen to prevent oxidation of the rod surface.

[0016] In a preferred or optional embodiment, in step S4, the cooling water inlet temperature of the crystallizer is 30-40° C., the outlet temperature is 50-60° C., the cooling water pressure is 0.04-0.08 MPa, and the cast rod outlet temperature is 300-500° C. The inlet and outlet temperature difference of the cooling water of the crystallizer is controlled within a suitable range to ensure the efficiency and quality of crystallization.

[0017] In a preferred or optional embodiment, in step S4, the drawing pitch is 5-6 mm, the pulling speed is 200-350 mm / min, and the dwell time is 800 ms-1200 ms. The horizontal continuous casting process is adopted, with high production efficiency and excellent machining performance of the prepared rods.

[0018] In a preferred or optional embodiment, the copper raw material is waste bronze without moisture. The present invention is particularly suitable for producing tin-lead-zinc bronze bars using waste bronze. Selecting the raw material as dry material without moisture can prevent melt aspiration and avoid pits on the surface of the bar.

[0019] In a preferred or optional embodiment, in step S2, the temperature of the medium frequency melting furnace is controlled at 1200-1220° C., in step S3, the temperature of the medium frequency melting furnace is controlled at 1100-1150° C., and in step S4, the temperature of the holding furnace is controlled at 1250-1280° C. Melting is controlled at a lower temperature to reduce the air absorption strength of the high-temperature melt and avoid problems such as cracking and pores. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the structure of the flux diffusion tooling in a specific implementation manner of the present invention.

[0021] Figure 2 It is a cross-sectional view of a crystallizer in a specific embodiment of the present invention.

[0022] Figure 3 for Figure 2 A partial enlarged view of point A in the middle.

[0023] Figure 4 This is a distribution diagram of various elements of the tin-lead-zinc bronze rod prepared in Example 1 of the present invention.

[0024] Figure 5 This is a metallographic diagram of the tin-lead-zinc bronze rod prepared in Example 1 of the present invention.

[0025] Figure 6 This is an appearance diagram of the tin-lead-zinc bronze rod prepared in Comparative Example 1 of the present invention.

[0026] Figure 7 This is a metallographic diagram of the tin-lead-zinc bronze rod prepared in Comparative Example 1 of the present invention.

[0027] Description of reference numerals:

[0028] 11-mixing chamber, 12-diffusion pipe, 13-spraying hole, 14-powder conveying pipe, 15-air flotation mesh plate, 16-nitrogen pipe, 17-feeder, 21-first outer shell, 22-first inner sleeve, 23-first sleeve, 24-separation ring, 25-first water inlet cavity, 26-first water outlet cavity, 27-first water inlet pipe, 28-first water outlet pipe, 29-cooling cavity, 31-second outer shell, 32-second sleeve, 33-second water inlet cavity, 34-second water inlet pipe, 35-second water inlet channel, 36-second water outlet channel, 41-water outlet sleeve, 42-second water outlet pipe, 5-nitrogen channel, 6-graphite mold. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0030] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] It should be noted that similar symbols and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, it does not require further definition and explanation in the subsequent drawings.

[0032] The specific embodiment of the present invention provides a tin-lead-zinc bronze rod, the main chemical components of which are Sn 4%-6%, Zn 4.5-6.0%, Pb 4.0-5.7%, impurities, and the balance is copper. The chemical composition is shown in the following table.

[0033] Table 1 Tin-lead-zinc bronze alloy material composition

[0034] Sn P Fe Zn Pb Ni other Cu 4.0-6.0 0.01-0.05 <0.3 4.5-6.0 4.0-5.7 <1.5 <0.1 margin

[0035] The production method of tin-lead-zinc bronze bars comprises the following steps:

[0036] S1. Add copper raw materials into a medium frequency melting furnace for melting.

[0037] In a specific embodiment, the raw material used is scrap bronze. The raw material with moisture is picked out by selection to ensure that the raw material is dry material without moisture, which can prevent the melt from absorbing air and avoid pits on the surface of the rod.

[0038] S2. After the copper raw material is melted, the slag cleaning agent, refining agent and refiner are added into the medium frequency melting furnace by using flux diffusion tooling. During this process, the temperature in the furnace is controlled at 1200-1220℃.

[0039] The above-mentioned refiner is composed of nitride, carbide and oxide, the mass fraction of nitride in the refiner is 20-35%, the mass fraction of carbide is 20-35%, and the mass fraction of oxide is 35-50%. The nitride is selected from one or two of titanium nitride TiN and aluminum nitride AlN, the carbide is selected from one or two of tungsten carbide WC and vanadium carbide VC, and the oxide is α-Al2O3. The refiner has ultra-high temperature stability and can form heterogeneous nucleation at the melting temperature, which is conducive to grain refinement, thereby making tin and lead evenly distributed and reducing the degree of segregation. Preferably, the amount of the refiner is 0.1-0.8% of the mass of the melt.

[0040] The structure of the flux diffusion tooling is as follows Figure 1 As shown, the flux diffusion tooling includes a mixing chamber 11 and a diffusion tube 12, and the mixing chamber 11 is connected to the diffusion tube 12 through a powder delivery tube 14, and a valve is provided on the powder delivery tube 14. The mixing chamber 11 is used for mixing powders such as slag cleaning agent, refining agent, and refiner. A feed port is provided on the top of the mixing chamber 11, and a feeder is provided on the feed port. An air inlet is provided on the side of the mixing chamber 11, and an air blowing port is provided at the bottom. An air flotation mesh plate 15 is provided inside, and a plurality of air jet holes are provided on the air flotation mesh plate 15. The air inlet and the air blowing port are connected to a nitrogen pipe 16, and a valve is provided on the nitrogen pipe 16. The diffusion tube 12 is provided with a plurality of injection holes 13 along the length direction, which can extend into the melt and spray the powder from the injection holes 13. The flux diffusion tooling is used as follows: first, the flux is added into the mixing chamber 11 from the feeder, and high-pressure nitrogen (0.1-0.2MPa) is blown into the mixing chamber 11 from the air flotation mesh plate 15 to mix the powders evenly, and then the mixed flux is blown into the diffusion tube 12 by nitrogen and sprayed out from the spray hole 13, so that the flux is evenly distributed in the melt, improving the refinement and refining effects.

[0041] S3. Take samples from the medium frequency melting furnace for component testing. After sampling, lower the temperature to 1130-1150℃, dilute or compensate according to the components, and selectively add copper, tin ingots, lead ingots, and zinc ingots; after sufficient stirring, conduct a second component test until the test is qualified. During the process, the smelting temperature is controlled at 1100-1150℃.

[0042] S4. Transfer the molten copper to the holding furnace and test the composition of the melt in the holding furnace. The temperature of the holding furnace is controlled at 1250-1280℃. The smelting temperature is controlled at a low level during the production process, thereby reducing the air absorption strength of the high-temperature melt and avoiding problems such as cracking and pores. Horizontal continuous casting is used for drawing, with a drawing pitch of 5-6mm, a pulling speed of 200-350mm / min, and a pause time of 800ms-1200ms.

[0043] In a specific embodiment, the structure of the crystallizer used for casting is as follows: Figure 2 and Figure 3As shown, the crystallizer includes a primary cooling fixture, a secondary cooling fixture and a water outlet sleeve 41 connected in sequence, the casting holes of the primary cooling fixture and the secondary cooling fixture are connected, and a graphite mold 6 is arranged in the primary cooling fixture. The primary cooling fixture includes a first outer shell 21, a first inner sleeve 22 and a first sleeve 23 arranged in sequence from the outside to the inside, and a separator ring 24 is arranged between the first outer shell 21 and the first inner sleeve 22. The separator ring 24 divides the space between the first outer shell 21 and the first inner sleeve 22 into a first water inlet chamber 25 and a first water outlet chamber 26. The first water inlet chamber 25 is connected to two first water inlet pipes 27, the first water outlet chamber 26 is connected to two first water outlet pipes 28, and the space between the first inner sleeve 22 and the first sleeve 23 constitutes a cooling chamber 29. After the cooling water enters from the first water inlet pipe 27, it passes through the first water inlet chamber 25, the cooling chamber 29 and the first water outlet chamber 26 in sequence, and flows out from the first water outlet pipe 28. Since the gap between the first inner sleeve 22 and the first sleeve 23 is very small, the cooling effect can be maximized, thereby reducing the segregation of tin and lead.

[0044] The secondary cooling fixture includes a second shell 31 and a second sleeve 32 arranged from outside to inside. The space between the second shell 31 and the second sleeve 32 constitutes a second water inlet chamber 33, and the second water inlet chamber 33 is connected to two second water inlet pipes 34. A second water inlet channel 35 is formed between the second sleeve 32 and the primary cooling fixture, and a second water outlet channel 36 is formed between the second sleeve 32 and the water outlet sleeve 41. The second water inlet channel 35 and the second water outlet channel 36 are connected to the second water inlet chamber 33, and the water outlet sleeve 41 is connected to the second water outlet pipe 42. When the crystallizer is working, the two second water inlet pipes 34 are simultaneously filled with water, which can provide high-pressure secondary water flow and form a water seal area for strengthening axial cooling and isolating the entry of oxygen. Excess water is discharged from the second water outlet pipe 42.

[0045] During the casting process, the cooling water inlet temperature of the crystallizer is 30-40℃, the outlet temperature is 50-60℃, the cooling water pressure is 0.04-0.08MPa, and the cast rod outlet temperature is 300-500℃. The temperature difference between the cooling water inlet and outlet of the crystallizer is controlled within an appropriate range to ensure the efficiency and quality of crystallization.

[0046] Preferably, a nitrogen channel 5 is provided on the crystallizer, and a nitrogen port of the nitrogen channel 5 is arranged at the connection position of the primary cooling tooling and the secondary cooling tooling. Filling nitrogen from the nitrogen channel 5 can form secondary gas protection, effectively avoiding oxidation of the rod surface.

[0047] The above method is designed to solve the problem that lead gravity segregation and tin reverse segregation are prone to occur in the local structure of tin-lead-zinc bronze bars. The method adopts grain refinement combined with enhanced cooling intensity to reduce the occurrence of segregation. Specifically, through technical means such as raw material selection, diffusion and addition of refiners into the melt, and change of crystallizer structure to enhance cooling intensity, efficient production of tin-lead-zinc bronze bars is achieved, and tin-lead-zinc bronze bars with low segregation degree, good surface quality and excellent machining performance can be prepared.

[0048] The technical solutions and effects of the present invention are illustrated below with reference to specific embodiments.

[0049] The raw materials used in the following examples are scrap mechanical copper. The tensile elongation test method in the examples is in accordance with "GB / T228-2002 Room temperature tensile test method for metal materials"; the hardness test method is in accordance with "GB / T4340.1-1999 Metal Vickers hardness test Part 1: Test method"; the grain size test method is in accordance with "GB / T 36165-2018 Determination of average grain size of metals"; the metallographic segregation test method is in accordance with "GB / T 224-2008 Determination of the depth of decarburized layer of steel".

[0050] Example 1

[0051] The main chemical components of the tin-lead-zinc bronze rod in this embodiment are Sn 4.2%, Zn 5.5%, Pb 5.2%, and the balance is copper. The specific chemical composition is shown in the following table.

[0052] Table 2 Alloy material composition of Example 1

[0053] Sn P Fe Zn Pb Ni Cu 4.2 0.04 - 5.5 5.2 1.4 margin

[0054] The method for preparing the tin-lead-zinc bronze rod comprises the following steps:

[0055] (1) Select the scrap bronze without moisture and melt it in a 1t medium frequency melting furnace.

[0056] (2) After the copper raw material is melted, a slag cleaning agent, a refining agent and a refiner are added into a medium frequency melting furnace using a flux diffusion tool. The refiner is composed of titanium nitride, tungsten carbide and α-Al2O3 in a mass ratio of 3:3:4. During this process, the temperature in the furnace is controlled at 1200-1220°C.

[0057] (3) Take samples from the medium frequency melting furnace for composition testing. After sampling, lower the temperature to 1130-1150°C, dilute or compensate according to the composition, and selectively add copper, tin ingots, lead ingots, and zinc ingots; after sufficient stirring, conduct a second composition test until the test is qualified. The process smelting temperature is controlled at 1100-1150°C.

[0058] (4) The molten copper was transferred to a holding furnace, and the composition of the melt in the holding furnace was tested. The temperature of the holding furnace was controlled at 1250-1280°C. Horizontal continuous casting was used for drawing, with a drawing pitch of 6 mm, a pulling speed of 300 mm / min, a dwell time of 1000 ms, a crystallizer cooling water inlet / outlet temperature of 40°C / 50°C, a cooling water pressure of 0.05 MPa, and a cast rod outlet temperature of 400°C.

[0059] The surface of the rod prepared in this example is smooth and has no pits. The distribution of copper, zinc, tin and lead in the material is observed respectively. The results are as follows: Figure 4 As shown, it shows that the gravity segregation of lead and the reverse segregation of tin in the alloy have been greatly improved, and the elements are evenly distributed without abnormal agglomeration. Figure 5 As shown, it can be seen that the α+δ eutectoid phase and the Pb particles are refined and uniform.

[0060] The test properties of the rod are as follows: tensile strength 470MPa, hardness 89Hv, elongation 33%, grain size 0.025um, surface inverse segregation layer thickness 0.014mm, roughness 0.9um.

[0061] Example 2

[0062] The main chemical components of the tin-lead-zinc bronze rod in this embodiment are Sn 4.4%, Zn 5.6%, Pb 5.0%, and the balance is copper. The specific chemical composition is shown in the following table.

[0063] Table 3 Composition of alloy materials in Example 2

[0064] Sn P Fe Zn Pb Ni Cu 4.4 0.04 - 5.6 5.0 margin 4.4

[0065] The method for preparing the tin-lead-zinc bronze rod comprises the following steps:

[0066] (1) Select the scrap bronze without moisture and melt it in a 1t medium frequency melting furnace.

[0067] (2) After the copper raw material is melted, a slag cleaning agent, a refining agent and a refiner are added into a medium frequency melting furnace using a flux diffusion tool. The refiner is composed of aluminum nitride, vanadium carbide and α-Al2O3 in a mass ratio of 3:3:4. During this process, the temperature in the furnace is controlled at 1200-1220°C.

[0068] (3) Take samples from the medium frequency melting furnace for composition testing. After sampling, lower the temperature to 1130-1150°C, dilute or compensate according to the composition, and selectively add copper, tin ingots, lead ingots, and zinc ingots; after sufficient stirring, conduct a second composition test until the test is qualified. The process smelting temperature is controlled at 1100-1150°C.

[0069] (4) The molten copper was transferred to a holding furnace, and the composition of the melt in the holding furnace was tested. The temperature of the holding furnace was controlled at 1250-1280°C. Horizontal continuous casting was used for drawing, with a drawing pitch of 5-6 mm, a pulling speed of 250 mm / min, a dwell time of 900 ms, a crystallizer cooling water inlet / outlet temperature of 35°C / 50°C, a cooling water pressure of 0.06 MPa, and a cast rod outlet temperature of 350°C.

[0070] The surface of the rod prepared in this embodiment is smooth and has no pits. The test performance is as follows: tensile strength 420MPa, hardness 89Hv, elongation 35%, grain size 0.03um, surface reverse segregation layer thickness 0.015mm, roughness 1.0um.

[0071] Example 3

[0072] The main chemical components of the tin-lead-zinc bronze rod in this embodiment are Sn 4.0%, Zn 5.8%, Pb 5.0%, and the balance is copper. The specific chemical composition is shown in the following table.

[0073] Table 4 Alloy material composition of Example 1

[0074] Sn P Fe Zn Pb Ni Cu 4.0 0.05 - 5.8 5.0 margin 4.0

[0075] The method for preparing the tin-lead-zinc bronze rod comprises the following steps:

[0076] (1) Select the scrap bronze without moisture and melt it in a 1t medium frequency melting furnace.

[0077] (2) After the copper raw material is melted, a slag cleaning agent, a refining agent and a refiner are added into a medium frequency melting furnace using a flux diffusion tool. The refiner is composed of titanium nitride, aluminum nitride, tungsten carbide and α-Al2O3 in a mass ratio of 1:2:3:4. During this process, the temperature in the furnace is controlled at 1200-1220°C.

[0078] (3) Take samples from the medium frequency melting furnace for composition testing. After sampling, lower the temperature to 1130-1150°C, dilute or compensate according to the composition, and selectively add copper, tin ingots, lead ingots, and zinc ingots; after sufficient stirring, conduct a second composition test until the test is qualified. The process smelting temperature is controlled at 1100-1150°C.

[0079] (4) The molten copper is transferred to a holding furnace, and the composition of the melt in the holding furnace is tested. The temperature of the holding furnace is controlled at 1250-1280°C. Horizontal continuous casting is used for drawing, with a drawing pitch of 5-6 mm, a pulling speed of 350 mm / min, a dwell time of 1200 ms, a crystallizer cooling water inlet / outlet temperature of 30°C / 60°C, a cooling water pressure of 0.04 MPa, and a cast rod outlet temperature of 500°C.

[0080] The surface of the rod prepared in this embodiment is smooth and has no pits. The test performance is as follows: tensile strength 470MPa, hardness 88Hv, elongation 33%, grain size 0.025um, surface reverse segregation layer thickness 0.014mm, roughness 0.9um.

[0081] Comparative Example 1

[0082] The main chemical components of the tin-lead-zinc bronze rod in this comparative example are Sn 4.2%, Zn 5.5%, Pb 5.2%, and the balance is copper. The specific chemical composition is shown in the following table.

[0083] Table 5 Alloy material composition of comparative example 1

[0084] Sn P Fe Zn Pb Ni Cu 4.2 0.04 - 5.5 5.2 1.4 margin

[0085] The method for preparing the tin-lead-zinc bronze rod comprises the following steps:

[0086] (1) Select the scrap bronze without moisture and melt it in a 1t medium frequency melting furnace.

[0087] (2) After the copper raw material is melted, the slag removal agent and refining agent are added into the medium frequency melting furnace, and the slag removal and refining are carried out by pressing with a pressure spoon. During this process, the temperature in the furnace is controlled at 1200-1220℃.

[0088] (3) Take samples from the medium frequency melting furnace for composition testing. After sampling, lower the temperature to 1130-1150°C, dilute or compensate according to the composition, and selectively add copper, tin ingots, lead ingots, and zinc ingots; after sufficient stirring, conduct a second composition test until the test is qualified. The process smelting temperature is controlled at 1100-1150°C.

[0089] (4) The molten copper was transferred to a holding furnace, and the composition of the melt in the holding furnace was tested. The temperature of the holding furnace was controlled at 1250-1280°C. Horizontal continuous casting was used for drawing. The crystallizer used was a common crystallizer. The drawing pitch was 6 mm. The pulling speed was 300 mm / min. The dwell time was 1000 ms. The crystallizer cooling water inlet / outlet temperature was 40°C / 50°C. The cooling water pressure was 0.05 MPa. The casting rod outlet temperature was 400°C.

[0090] The appearance of the rod prepared in Comparative Example 1 is as follows Figure 6 As shown, the surface is rough and has pits; its metallographic structure is as follows Figure 7 As shown, it is composed of α+(α+δ)+Pb. Since there are still hidden cracks in the bar after straightening, and even they have expanded, during the grinding process, the bar is subjected to strong circumferential shear stress and encounters hard and brittle phases, which means that the surface material of the bar will collapse in blocks, resulting in the phenomenon of lack of meat (pits). Figure 5 and Figure 7By comparison, it can be seen that after adding refiner to the alloy, the α+δ eutectoid phase and Pb particles are finer and more uniform than before the modification treatment. At the same time, from the microstructure before and after the refinement treatment, it can be concluded that the mechanical properties of the cast rod after the refinement treatment are more stable and better than those before the treatment.

[0091] The test properties of the rod prepared in Comparative Example 1 are as follows: tensile strength 300 MPa, hardness 68 Hv, elongation 18%, grain size 0.05 um, surface reverse segregation layer thickness 0.25 mm, roughness 3.2 um.

[0092] The performance test results of each embodiment and comparative example are shown in the following table. It can be seen that compared with the comparative example, the rods prepared in the embodiments of the present invention have a low degree of segregation, good surface quality, and significantly improved machining performance.

[0093] Table 6 Performance test results of the embodiments of the present invention and the comparative examples

[0094]

[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for producing tin-lead-zinc bronze bars, characterized in that: The following steps are involved: S1. Add copper raw materials into a medium frequency melting furnace for melting; S2. After the copper raw material is melted, a slag cleaning agent, a refining agent and a refiner are added into a medium frequency melting furnace by a flux diffusion tool, wherein the refiner is composed of nitride, carbide and oxide, wherein the nitride is titanium nitride and / or aluminum nitride, the carbide is tungsten carbide and / or vanadium carbide, and the oxide is α-Al2O3; S3. Take samples from the medium frequency melting furnace for testing, dilute or compensate according to the composition, selectively add copper, tin ingots, lead ingots, and zinc ingots, and control the alloy to contain the following mass percentages: 4.0-6.0% Sn, 0.01-0.05% P, <0.3% Fe, 4.5-6.0% Zn, 4.0-5.7% Pb, <1.5% Ni, <0.1% unavoidable impurities, and the balance is Cu; S4. After transferring the molten copper to a holding furnace, horizontal continuous casting is used for drawing to obtain tin-lead-zinc bronze rods. The crystallizer used for horizontal continuous casting includes a primary cooling tool, a secondary cooling tool and a water outlet sleeve connected in sequence. The casting holes of the primary cooling tool and the secondary cooling tool are connected. The primary cooling tool includes a first outer shell, a first inner sleeve and a first sleeve arranged in sequence from the outside to the inside. A separator ring is provided between the first outer shell and the first inner sleeve. The separator ring separates the space between the first outer shell and the first inner sleeve into a first water inlet chamber and a first water outlet chamber. The first water inlet chamber is connected to at least one first water inlet pipe. The first water outlet cavity is connected to at least one first water outlet pipe, and the space between the first inner sleeve and the first sleeve constitutes a cooling cavity. The secondary cooling tooling includes a second outer shell and a second sleeve arranged from outside to inside, and the space between the second outer shell and the second sleeve constitutes a second water inlet cavity. The second water inlet cavity is connected to at least one second water inlet pipe. A second water inlet channel is formed between the second sleeve and the primary cooling tooling, and a second water outlet channel is formed between the second sleeve and the water outlet sleeve. The second water inlet channel and the second water outlet channel are connected to the second water inlet cavity, and the water outlet sleeve is connected to at least one second water outlet pipe.

2. The method for producing tin-lead-zinc bronze bars according to claim 1, characterized in that: In the refiner, the mass fraction of the nitride is 20-35%, the mass fraction of the carbide is 20-35%, and the mass fraction of the oxide is 35-50%.

3. The method for producing tin-lead-zinc bronze bars according to claim 2, characterized in that: In the step S2, the amount of the refiner used is 0.1-0.8% of the mass of the melt.

4. The method for producing tin-lead-zinc bronze bars according to claim 1, characterized in that: The flux diffusion tooling includes a mixing chamber and a diffusion tube, the mixing chamber is connected to the diffusion tube through a powder conveying tube, the diffusion tube is provided with a plurality of injection holes along the length direction, the mixing chamber is provided with a feed port at the top, an air inlet at the side, and an air blowing port at the bottom, the mixing chamber is provided with an air flotation mesh plate, the air flotation mesh plate is provided with a plurality of injection holes, and the air inlet and the air blowing port are connected to a nitrogen pipe.

5. The method for producing tin-lead-zinc bronze bars according to claim 1, characterized in that: A nitrogen port is provided at the connection position between the primary cooling fixture and the secondary cooling fixture, and a nitrogen channel connected to the nitrogen port is provided on the crystallizer.

6. The method for producing tin-lead-zinc bronze bars according to claim 5, characterized in that: In step S4, the cooling water inlet temperature of the crystallizer is 30-40°C, the outlet temperature is 50-60°C, the cooling water pressure is 0.04-0.08MPa, and the cast rod outlet temperature is 300-500°C.

7. The method for producing tin-lead-zinc bronze bars according to claim 6, characterized in that: In the step S4, the drawing pitch is 5-6 mm, the pulling speed is 200-350 mm / min, and the pause time is 800 ms-1200 ms.

8. The method for producing tin-lead-zinc bronze bars according to claim 1, characterized in that: The copper raw material is waste bronze without moisture.

9. The method for producing tin-lead-zinc bronze bars according to claim 8, characterized in that: In the step S2, the temperature of the medium frequency melting furnace is controlled at 1200-1220°C, in the step S3, the temperature of the medium frequency melting furnace is controlled at 1100-1150°C, and in the step S4, the temperature of the holding furnace is controlled at 1250-1280°C.

Citation Information

Patent Citations

  • Preparation method of copper alloy, and copper alloy obtained by the method, application of copper alloy, electronic element and mechanical element

    CN111893332A

  • Preparation method of tin bronze cast ingot

    CN115846599A